Analysis for fluid-elastic instability of tube arrays in cross-flow - Masahiko UTSUMI (Mechanical Engineering Journal, 2015)
To date, no study has been conducted on analytical methods to solve the fluid dynamics governing equations system for the fluid-elastic vibration of tube arrays in a straightforward manner. In this paper, a semi-analytical method for this vibration problem is investigated by considering the system as a collection of regular polygon cells and expressing unknowns on each side of the cells by base expansion. Based on this expression, the solutions in the cell are expressed in terms of polar coordinates, allowing for circumferential variation in the radial coordinate interval. Via this means, a reduced-order model is developed for the tube array-fluid system and the proposed method is verified by comparing with earlier experimental results.